Metabolic Syndrome and Bone Density in Obese Adolescents - Sukmasari, Vintantiana; Dieny, Fillah Fithra; Panunggal, Binar (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
The purpose of this study was to analyse the correlations of metabolic syndrome components (central obesity, triglyceride levels, and hypertension) and related factors including nutrient intake and bone physical activity with bone density in obese adolescents. A cross-sectional study was conducted involving 47 obese adolescents (15-18 years) from three high schools in Semarang city, Central Java, selected by consecutive sampling. Bone density was measured by the Quantitative Ultrasound method. Metabolic syndrome and osteopenia were detected in 28% and 11% subjects, respectively. Positive correlations were found between triglyceride levels, calcium intake, vitamin D intake, current bone-physical activity (cBPA) and bone density (p<0.05). Conversely, central obesity, blood pressure, protein intake, animal protein, plant protein, phosphorus, potassium, sodium, past bone-physical activity (pBPA), and total bone-physical activity (tBPA) were not correlated with bone density. It was found that calcium intake, cBPA, and triglyceride levels were the two strongest factors related to bone density (adjusted R2=52.5%). This study showed that obese adolescents are at risk of having metabolic syndrome and higher triglyceride levels imply lower bone density.